My pronouns are they/them: Talking about pronouns changes how pronouns are understood - Arnold, Jennifer E. (Psychon Bull Rev, 2021)
The pronoun “they” can be either plural or singular, perhaps referring to an individual who identifies as nonbinary. How do listeners identify whether “they” has a singular or plural sense? We test the role of explicitly discussing pronouns (e.g., “Alex uses they/them pronouns”). In three experiments, participants read short stories, like “Alex went running with Liz. They fell down.” Answers to “Who fell down” indicated whether participants interpreted they as Alex or Alex-and-Liz. We found more singular responses in discourse contexts that make Alex more available: when Alex was either the only person in the context or mentioned first. Critically, the singular interpretation was stronger when participants heard explicit instructions that Alex uses they/them pronouns, even though participants in all conditions had ample opportunity to learn this fact through observation. Results show that the social trend to talk about pronouns has a direct impact on how language is understood.